2008
DOI: 10.1016/j.jsat.2007.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine dependence and human immunodeficiency virus risk behavior

Abstract: We examined human immunodeficiency virus (HIV) related risk behaviors among methamphetamine (MA) dependent users. Secondary data analysis was performed on data from a large clinical trial: the Methamphetamine Treatment Project (MTP) (N=784). All MA-dependent participants were enrolled in an outpatient treatment program, receiving either a standard psychosocial intervention (Matrix Model) or Treatment-as-Usual. HIV-related risk behavior, including injection and unsafe sexual practices, was assessed using the AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Health policy makers should consider ATS education as a health priority. Studies have shown that drug education is necessary to prevent the epidemic of any type of drug (17)(18)(19). Furthermore, law enforcement and police efforts should target ceasing ATS production and distribution in the Persian community on a large scale.…”
Section: Discussionmentioning
confidence: 99%
“…Health policy makers should consider ATS education as a health priority. Studies have shown that drug education is necessary to prevent the epidemic of any type of drug (17)(18)(19). Furthermore, law enforcement and police efforts should target ceasing ATS production and distribution in the Persian community on a large scale.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and behavioral research on MA-dependent individuals indicates that they may be especially vulnerable to poor HRQOL outcomes. The chronic and long-term use of MA has been linked to substantial medical illness and disability, including cardiopulmonary consequences (chest pain, hypertension, shortness of breath, and tachycardia; Rawson, Gonzales, & Ling, 2006), impaired cognitive functioning (slower motor function, decreased memory and attention, and impulsivity; McKetin & Mattick, 1998;Semple, Zians, Grant, & Patterson, 2005), severe psychiatric comorbidity (psychosis, persecutory delusions, ideas of reference, persistent visual and auditory hallucinations, depression, anxiety, and suicidal ideation; Glasner-Edwards et al, in press;Meredith, Jaffe, Ang-Lee, & Saxon, 2005;Wells et al, 1989;Zweben et al, 2004), increased risky behaviors (transmission and infection of HIV; hepatitis A, B, and C; and other sexually transmitted infections; Gonzales et al, 2008;Rawson et al, 2008), and substantial criminal involvement (Evans & Longshore, 2004;Farabee, Prendergast, & Cartier, 2002;Griffin, Rabkin, Remein, & Williams, 1998;Iguchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…no condom use and anal sex) than persons who use other drugs. 7,8 The analysis of the findings from the eight studies conducted in Cape Town, however, found less consistent findings of an association between MA use and having sex without a condom, with several studies indicating an association 10,11,12,15 and others not. 3,10,15 The one study which found that MA use was more associated with condom use 11 , also found that MA users were less likely to have sex under the influence of alcohol or other drugs in contrast to three studies that found the opposite.…”
Section: Discussionmentioning
confidence: 94%
“…8 Research among heterosexual populations has, for example, shown that MAdependent users have more sexual partners and participate in more risky sexual behaviour (i.e. no condom use and anal sex) than persons who use other drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation